Beyond Exposure to Outdoor Nature: Exploration of the Benefits of a Green Building’s Indoor Environment on Wellbeing - Dreyer, Bianca C.; Coulombe, Simon; Whitney, Stephanie; Riemer, Manuel; Labbé, Delphine (Frontiers in Psychology, 2018)
Most research exploring the psychological benefits of the natural environment has focused on direct exposure to the outdoors. However, people spend most of their time indoors, particularly in office buildings. Poor employee mental health has become one the most prevalent and costly occupational health issues. The integration of high quality environmental features (e.g., access to sunlight) in green-certified office buildings offers a superior work environment. These nature-based experiences are anticipated to provide beneficial outcomes to wellbeing. This study is the first to empirically investigate these benefits. Participants in a green (LEED gold certified) office building (N = 213) in Canada completed an assessment of environmental features, measures of hedonic, eudaimonic and negative wellbeing and assessments of psycho-environmental potential, environmental behaviors and social belonging. Linear regression analyses confirmed the benefits of indoor environmental features for all aspects of wellbeing. Multiple regression analyses were conducted to assess the effect of specific indoor environmental features on wellbeing. We explored physical features (e.g., air quality, light), and social features (e.g., privacy), as well as windows to the outside. Results suggest that physical features are important in promoting hedonic wellbeing, while social features prevent negative wellbeing. Both features equally predicted eudaimonic wellbeing. A view to the outside was positively correlated to wellbeing, although it did not uniquely predict it after accounting for other environmental features. Path analyses revealed the importance of person-environment fit, pro-environmental behavior and social belonging in mediating the association of indoor environmental features with hedonic and eudaimonic wellbeing. The results suggests that, by fostering person-environment fit, pro-environmental behaviors and feeling of community in a high quality setting, green buildings may lead to benefits on an array of wellbeing dimensions. The theoretical and practical implications of these findings are discussed.